Multi-Agent Deep Deterministic Policy Gradient Algorithm Based on Classification Experience Replay - Sun, Xiaoying; Chen, Jinchao; Du, Chenglie; Zhan, Mengying (IEEE Advanced Information Technology, Electronic and Automation Control Conference (IAEAC) (Online), 2022)
In recent years, multi-agent reinforcement learning has been applied in many fields, such as urban traffic control, autonomous UAV operations, etc. Although the Multi-Agent Deep Deterministic Policy Gradient (MADDPG) algorithm has been used in various simulation environments as a classic reinforcement algorithm, its training efficiency is low and the convergence speed is slow due to its original experience playback mechanism and network structure. The random experience replay mechanism adopted by the algorithm breaks the time series correlation between data samples. However, the experience replay mechanism does not take advantage of important samples. Therefore, the paper proposes a Multi-Agent Deep Deterministic Policy Gradient method based on classification experience replay, which modifies the traditional random experience replay into classification experience replay. Classified storage can make full use of important samples. At the same time, the Critic network and the Actor network are updated asynchronously, and the learned better Critic network is used to guide the Actor network update. Finally, to verify the effectiveness of the proposed algorithm, the improved algorithm is compared with the traditional MADDPG method in a simulation environment.